Imaging of Dental Hard Tissue Surfaces Prepared by an Ultrashort Pulsed Laser System (USPL). (12th December 2016) - Schäper, Matthias; Reimann, Susanne; Frentzen, Matthias; Meister, Jörg
Abstract: The aim of this study was to compare surface structures of laser-irradiated dental hard tissues using confocal (CFM), atomic force (AFM), and scanning electron microscopy (SEM). The general potential of the AFM in analyzing laser-irradiated surfaces was determined in this context. Specimens of human enamel and dentin were irradiated using an 8.6 W Nd:YVO4 laser with a pulse duration of 8 ps, λ Center =1, 064 nm, and a pulse repetition rate of 500 kHz. Surface topology of irradiated areas (1 mm 2 ) was investigated using AFM, CFM, and SEM. Surface roughness R z was measured only with the AFM and the CFM. For non-irradiated enamel and dentin surfaces, roughnesses for CFM and AFM are in the nanometer range. However, major differences in roughness were determined for laser-prepared surfaces. For enamel, R z (CFM)=2.33 μ m is much higher compared with R z (AFM)=0.09 μ m; in the case of dentin, R z (CFM)=5.35 μ m is also much higher compared with R z (AFM)=0.093 μ m. Information regarding structural properties of surfaces needs real dimensions, particularly for use in dentistry. In this respect, AFM technology provides no additional results that lead to a significant improvement.